We're in This Together: Intergenerational Health Policies as an Emerging Public Health Necessity - Plagg, Barbara; Oschmann, Jörg; Engl, Adolf; Piccoliori, Giuliano; Conca, Andreas; Eisendle, Klaus (Frontiers in Human Dynamics, 2020)
The global handling of the COVID-19 pandemic has highlighted the lack of intergenerational public health solutions. Discontinuity of educational and health care services and environmental threats increase various pathologies and may provoke long-term health damage among the youngest. Unbalanced generational approaches within health policies have been evident before the pandemic and will continue to be a global challenge as both acute and chronic threats due to environmental hazards and social disparities are increasing. We therefore aim to bring with the present article the concept of intergenerational health to the center of socio-political attention as it must become beyond the COVID-19 crisis a core concept in the development and implementation of health policies.